2015
DOI: 10.1159/000381923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Long-Term Imatinib Therapy for Pulmonary Arterial Hypertension

Abstract: Background: Antiproliferative strategies have emerged as a potential therapeutic option for pulmonary arterial hypertension (PAH). Objective: To evaluate the long-term efficacy and safety of imatinib. Methods: This is an observational study of 15 patients with idiopathic PAH (n = 13) or PAH associated with connective tissue disease (n = 2) treated off-label with imatinib 400 mg daily. Pulmonary hypertension-specific therapy was established in all patients (triple therapy in 10, dual therapy in 3, and monothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…; Speich et al. ). Previous studies have focused on single pathways, and cross‐talk between different pathways needs more attention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Speich et al. ). Previous studies have focused on single pathways, and cross‐talk between different pathways needs more attention.…”
Section: Discussionmentioning
confidence: 97%
“…increased in both PAH animal models and patients (Benisty et al 2004;Izikki et al 2009). Inhibition of both PDGF and FGF signaling have been shown to ameliorate PAH, however, treatment of patients with their inhibitors was accompanied by severe adverse events and drug discontinuation was common (Frost et al 2015;Speich et al 2015). Previous studies have focused on single pathways, and cross-talk between different pathways needs more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Why does the right ventricle dilate in one PAH patient and not in the other? Although this question cannot be answered yet, it became clear from another recent study that the contractile reserve of the right ventricle in advanced stages of PAH is absent [28]. For this reason dilatation might be the only option for the right ventricle to preserve stroke volume.…”
Section: Novel Insights Into Treatment Strategy In Pahmentioning
confidence: 99%
“…As this agent also shows inhibitory effects on the plateletderived growth factor and c-KIT signaling, it was suggested that it may be efficacious in PAH, but it was not approved due to side effects and serious adverse events [18] . Patients who participated in the phase III trial often continued treatment with imatinib due to good clinical response and positive effects on quality of life [19] . 28 cation plasma concentrations in the Center for Pulmonary Hypertension, Thorax Clinic at the University Hospital Heidelberg.…”
Section: Introductionmentioning
confidence: 99%